Responding to COVID-19 threats to trial conduct: lessons learned from a feasibility trial of a psychological intervention for South African adolescents - Myers-Franchi, Bronwyn; van der Westhuizen, C.; Pool, M.; Hornsby, N.; Sorsdahl, K.R. (BMC, 2021)
The COVID-19 pandemic has posed challenges to the conduct of clinical trials. Strategies for overcoming common challenges to non-COVID-19 trial continuation have been reported, but this literature is limited to pharmacological intervention trials from high-income settings. The purpose of this paper is to expand the literature to include a low- and middle-income country perspective. We describe the challenges posed by COVID-19 for a randomised feasibility trial of a psychological intervention for adolescents in Cape Town, South Africa, and lessons learned when implementing strategies to facilitate trial continuation in this context. We used a Plan-Do-Study-Act cycle method to explore whether our adaptations were having the desired effect on trial accrual and retention. We found that stakeholder engagement, trial coordination and team communication need to be intensified while testing these procedural changes. We learned that strategies found to be effective in high-income countries required significant adaptation to our resource-constrained setting. The detailed documentation of extraneous influences, procedural changes and trial process information was essential to guiding decisions about which adaptations to retain. This information will be used to examine the potential impact of these changes on study outcomes. We hope that these reflections will be helpful to other trialists from low- and middle-income countries grappling with how to minimise the impact of public health emergencies on their research. Trial registration: The trial is registered with the Pan African Clinical Trials Registry (PACTR20200352214510). Registered 28 February 2020. https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=9795.